Penerapan Soil Preloading, PVD, dan PHD untuk Analisis Penurunan Konsolidasi Tanah - Andini, Citra Kusuma; Yelvi, Yelvi; Wahyu, Azmi Lisani; Sudardja, Handi; Misriani, Merley (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2023)
Soft clay has a low bearing capacity, high compressibility and low permeability. This condition causes soft clay soil to have a long settlement time. To overcome this soft soil condition, soil improvement methods are needed. One of the efforts is to use a combination of soil preloading methods, Prefabricated Vertical Drain (PVD), and Prefabricated Horizontal Drain (PHD) methods. Calculating soil settlement with soil improvement is carried out using the Asaoka method, which is a field observation method, and the theoretical method using the Terzaghi method. Based on the calculation results of field observations using the Asaoka method, the average degree of soil settlement is 93.5%. The calculation results of the Asaoka method are recalculated using a back calculation to produce a new parameter value, namely the horizontal consolidation (Ch) value, which is then compared with the Ch value in the previous plan. In the Terzaghi method, the average soil settlement value is 1.205 meters. The results of soil settlement value are used to analyze the height of the embankment based on the load ratio requirement in SNI 8460: 2017, where the load ratio on the ground is ≥ 1.3 times the planned load under service conditions. Based on the monitoring results, a load ratio value of 0.875 was obtained so that the SNI requirements carried out a re-planning of the landfill. Then, proceed with the design of PVD and PHD. The results obtained in planning use triangular PVD patterns with a distance between PVDs of 1 meter.